Validity of the Psychosocial Impact of Dental Aesthetics Questionnaire for use on Brazilian adolescents - Paula Mendes Santos; Alcides Ricardo Gonçalves; Tatiane Marega
ABSTRACT Introduction: The Psychosocial Impact of Dental Aesthetics Questionnaire (PIDAQ) is a multi-item psychometric instrument used to assess patients' perspective of the impact specifically related to Orthodontics. The cross-culturally adapted Brazilian version of the PIDAQ has demonstrated good reliability, validity and acceptability. Objective: The aim of the present study was to test the validity and reliability of the Brazilian version of the PIDAQ for use among adolescents aged between 11 and 14 years old. Methods: Having established the possibility of maintaining the operational characteristics of the Brazilian version of PIDAQ for the target age group, 194 individuals in the city of Belo Horizonte, Brazil, completed the questionnaire. The subjects were examined for the presence/absence of malocclusion based on the criteria of the Dental Aesthetic Index (DAI) to test discriminant validity. Internal consistency was measured by means of Cronbach's alpha coefficient which ranged from 0.59 to 0.86 for the subscales. Test-retest reliability was assessed by means of intraclass correlation coefficient which ranged from 0.54 to 0.89 for aesthetic concern and psychological impact. Results: Discriminant validity revealed that subjects without malocclusion had different PIDAQ scores in comparison to those with malocclusion. Conclusion: These findings suggest that the Brazilian version of PIDAQ for adolescents has satisfactory psychometric properties and is applicable to this age group in Brazil.